From ownership to custodianship: rethinking human biospecimens data governance in the Chinese context - Peng, Yifan; Li, Jiyuan; Lei, Ruipeng (Frontiers in Genetics, 2025)
As biomedical research shifts from being experiment-driven to data-driven, the importance of human biomedical data (HBD) has been increasingly highlighted. In this context, traditional data governance models face significant challenges. This paper, based on exploring the ontological and moral status of HBD, analyzes the limitations of the current ownership model and proposes a data governance framework centered on custodianship. The paper then highlights how custodianship aligns with Chinese culture, law, and the concept of “Responsible Research and Innovation (RRI)” through an analysis of current policies in the European Union (EU), the United States (US), and China, while also discussing the application of data trust as a specific implementation mechanism. Finally, the paper points out that transitioning to a custodianship model can more effectively balance privacy protection with innovation, data security with technological development, and data sharing with data protection, offering a new perspective and approach for China’s HBD governance and providing a Chinese solution for global HBD governance, thereby promoting the healthy development of life sciences and technology.